Design of UWB Filter with WLAN Notch - Harish Kumar; MD. Upadhayay (International Journal of Antennas and Propagation, 2012)
UWB technology- (operating in broad frequency range of 3.1–10.6 GHz) based filter with WLAN notch has shown great achievement for high-speed wireless communications. To satisfy the UWB system requirements, a band pass filter with a broad pass band width, low insertion loss, and high stop-band suppression are needed. UWB filter with wireless local area network (WLAN) notch at 5.6 GHz and 3 dB fractional bandwidth of 109.5% using a microstrip structure is presented. Initially a two-transmission-pole UWB band pass filter in the frequency range 3.1–10.6 GHz is achieved by designing a parallel-coupled microstrip line with defective ground plane structure using GML 1000 substrate with specifications: dielectric constant 3.2 and thickness 0.762 mm at centre frequency 6.85 GHz. In this structure a λ/4 open-circuited stub is introduced to achieve the notch at 5.6 GHz to avoid the interference with WLAN frequency which lies in the desired UWB band. The design structure was simulated on electromagnetic circuit simulation software and fabricated by microwave integrated circuit technique. The measured VNA results show the close agreement with simulated results.